Spillovers from EU law into national law: (un)intended consequences for private law relationships - Johnston, A (Hart Publishing, 2013)
The idea that European integration involves ‘spillover Effects’ is almost as old as the EU Treaties themselves: the evolution of the Treaties from the narrow beginnings of the European Coal and Steel Community (ECSC) in 1952 was predicted by some contemporary sages to be the result of various political and economic spillovers from the operation of the ECSC, its policies and institutions. While this evolutionary road was not always as smooth as some might have liked, the advent of the European Economic Community and the European Atomic Energy Community Treaties in 1957 can be seen as at least in part a response to the growing economic and political interaction between states in Europe; and the subsequent evolution of EU law at the EU legislative and judicial level has oft en been Effected by the use of Treaty bases to respond to social and economic developments precipitated by the application of the general rules of those Treaties over time.